Kemampuan Menemukan Gagasan Utama Pada Paragraf Dengan Metode Scaffolded Reading Berbasis Motivasi Membaca Siswa di Kelas IX SMP Negeri 2 Balaraja - Sari Apriyani; Juli Yani; Agus Sulaeman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research is motivated by: 1) the existence of various facts which show that students' reading comprehension abilities and reading motivation are relatively low; 2) the ability to find the main idea in a paragraph is very important in understanding a reading text. This research was carried out to determine the effect of the motivation-based Scaffolded Reading method on improving students' learning outcomes in finding the main idea in a paragraph. The research was carried out in class IX-C of SMPN 2 Balaraja. The method used in the research is an experimental method with a quantitative approach. After knowing the results of data analysis that the application of the scaffolded reading method is effective in improving the ability to find the main idea in a paragraph, it is best to use this technique as an alternative learning technique in learning reading comprehension to improve reading skills.